2002
DOI: 10.1002/em.10042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sodium arsenite on the genotoxicity of potassium dichromate and ethyl methanesulfonate: Studies with the wing spot test in Drosophila

Abstract: The wing spot test in Drosophila melanogaster was used to investigate the genotoxicity of arsenic and its effects on the action of two clearly genotoxic agents: potassium dichromate (PDC) and ethyl methanesulfonate (EMS). This assay is based on the principle that the loss of heterozygosity of the suitable recessive markers multiple wing hairs (mwh) and flare-3 (flr(3)) can lead to the formation of mutant clones of larval cells, which are then expressed as spots on the wings of adult flies. These spots can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…The average control frequency of mutant spots (0.26) was consistent with the normal background range reported by different authors [Frei and Würgler, 1995;Torres et al, 1998;Rizki et al, 2002]. Thus, in the wing spot test, CC does not appear to be genotoxic, which agrees with the only results previously reported in somatic cells of Drosophila using the zeste test [Rasmuson, 1985].…”
Section: Resultssupporting
confidence: 92%
“…The average control frequency of mutant spots (0.26) was consistent with the normal background range reported by different authors [Frei and Würgler, 1995;Torres et al, 1998;Rizki et al, 2002]. Thus, in the wing spot test, CC does not appear to be genotoxic, which agrees with the only results previously reported in somatic cells of Drosophila using the zeste test [Rasmuson, 1985].…”
Section: Resultssupporting
confidence: 92%
“…3b and 3c), which increases the background level of arsenic in the larvae (0.07 ng As/larva) 47-fold. This retention of high levels of inorganic arsenic was not accompanied by genotoxicity, as we demonstrated in a previous study [Rizki et al, 2002]. The lack of biomethylation does not mean that Drosophila are totally devoid of detoxication mechanisms for inorganic arsenic.…”
Section: Discussionsupporting
confidence: 66%
“…Arsenite also induces chromosome aberrations, endoreduplication, aneuploidy, and micronucleus formation [Gurr et al, 1993;Huang et al, 1995;Kochhar et al, 1996]. A recent study indicated that arsenite was not genotoxic in the somatic cells of D. melanogaster (wing spot test) [Rizki et al, 2002], confirming the results of Ramos-Morales and Rodriguez-Arnaiz [1995] in the same test system.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations